Genetic Polymorphisms Affecting IDO1 or IDO2 Activity Differently Associate With Aspergillosis in Humans - Napolioni, Valerio; Pariano, Marilena; Borghi, Monica; Oikonomou, Vasilis; Galosi, Claudia; De Luca, Antonella; Stincardini, Claudia; Vacca, Carmine; Renga, Giorgia; Lucidi, Vincenzina; Colombo, Carla; Fiscarelli, Ersilia; et al. (Frontiers in Immunology, 2019)
Aspergillus is the causative agent of human diseases ranging from asthma to invasive infection. Genetic and environmental factors are crucial in regulating the interaction between the host and Aspergillus. The role played by the enzyme indoleamine 2,3-dioxygenase 1 (IDO1), which catalyzes the first and rate-limiting step of tryptophan catabolism along the kynurenine pathway, is increasingly being recognized, but whether and how genetic variation of IDO1 influences the risk of aspergillosis in susceptible patients is incompletely understood. In addition, whether the closely related protein IDO2 plays a similar role remains unexplored. In the present study, we performed genetic association studies in two different cohorts of susceptible patients [cystic fibrosis (CF) patients and recipients of hematopoietic stem cell transplantation (HSCT)], and identified IDO1 polymorphisms that associate with the risk of infection in both cohorts. By using human bronchial epithelial cells and PBMC from CF and HSCT patients, respectively, we could show that the IDO1 polymorphisms appeared to down-modulate IDO1 expression and function in response to IFN or Aspergillus conidia, and to associate with an increased inflammatory response. In contrast, IDO2 polymorphisms, including variants known to profoundly affect protein expression and function, were differently associated with the risk of aspergillosis in the two cohorts of patients as no association was found in CF patients as opposed to recipients of HSCT. By resorting to a murine model of bone marrow transplantation, we could show that the absence of IDO2 more severely affected fungal burden and lung pathology upon infection with Aspergillus as compared to IDO1, and this effect appeared to be linked to a deficit in the antifungal effector phagocytic activity. Thus, our study confirms and extends the role of IDO1 in the response to Aspergillus, and shed light on the possible involvement of IDO2 in specific clinical settings.